SHUKA DHANYA VARGA (GROUP OF CEREALS): A PREVENTIVE AND CURATIVE PERSPECTIVE - Sharma, *Astha; Shukla, Shiv Shankar (International Journal of Ayurveda and Pharma Research, 2018)
Nutritious diet (Ahara) or we can say balanced diet is the key to follow the first principle of Ayurveda or in order to maintain a healthy life. In Ayurveda Acharya Charak has mentioned regular intake of food articles belongs to different categories of food. Acharya Charak has classified Ahara (diet) in twelve categories. Among these, Shukadhanya is the first one. In modern literature, Shukadhanya has been classified in monocotyledons and energy giving food. Energy giving food mainly includes cereal groups like wheat, rice, maize (corn), oats, Jowar, Ragi, and Bajra. Ancient Acharyas has mentioned some Shukadhanya dravyas with their gunas (qualities) like Shashthika, Vrihi (variety of rice), Yava, wheat, which play an important role in prevention of diseases. These Dravyas are Sheeta (cold in potency), Swadu (sweet in taste), Swadu Vipaka (Sweet in digestion). They are said to be Vatavardhak, Alpavarchasa, Brinhana, Shukrala and Mutral. In modern literature, Shukadhanya Varga has been classified in cereal group. Cereals are enriched with niacin, iron, riboflavin, and thiamine, and most cereals have abundant fibre content, especially barley, oat, and wheat. Cereals also have soluble bran that aids in lowering blood cholesterol level and helps in preventing heart diseases. This article is an attempt to analyze the Shukadhanya Varga mentioned in Ayurveda on a scientific basis.